A legal study on the procedure of registering polygamous marriages contracted abroad among muslim couples in the state of Selangor / Mohamad Isa Abd Ralip…[et al.] - Abd Ralip, Mohamad Isa; Mazelan, Mohd Mazanni; Mohd Paat, Mohd Sophian; Md Idros, Mohd Nooraizan; Che Izhar, Al Izaini (2010)
The procedures to register polygamous marriages in Selangor are very complicated and rigid. Therefore, most polygamous marriages are contracted abroad in order to avoid long and rigid procedure where it is normally perceived by contracted parties that contracted polygamous marriages abroad only need to register the polygamous marriages in the state and pay a fine of RM15000.00. But it is not the solution because such procedure is very time consuming and complicated. By referring to the Federal Territory (FT) procedures, the study suggests several processes that could be applied in Selangor, in order to make the procedure in Selangor more convenient and practical to the applicants of a polygamous marriage. The research is a library-based research where relevant Statutes are referred to. On top of that, the interview with the relevant authorities that consists of the court registrar, marriage registrar, Syarie Prosecutor, and Syarie Lawyers are also conducted.